ANALISIS PENGARUH HARGA, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE - Rizky Dwijantoro (2021)
This research uses a quantitative descriptive method that is carried out on the Shopee marketplace. The purpose of this research is to find out and prove whether purchasing decisions on the Shopee marketplace are influenced by Price, Product Quality and Promotion. The population in this study were students who had made purchases through Shopee. The sample taken in this study amounted to 75 respondents with purposive sampling method. By patiently taking the questionnaire through googleform. The analysis technique used is descriptive analysis and inferential analysis using Partial Least Square (PLS) analysis tool. The results showed that the variable price and product quality had an effect on purchasing decisions as well as promotion variables which had a positive and significant effect on purchasing decisions.